2006
DOI: 10.1097/01.inf.0000238143.96607.ec
|View full text |Cite
|
Sign up to set email alerts
|

A Community Outbreak of Conjunctivitis Caused by Nontypeable Streptococcus pneumoniae in Minnesota

Abstract: This outbreak was widespread in the community and conjunctivitis clinical presentation varied by age. The predominant strains in this outbreak were related to a pneumococcal strain implicated in prior conjunctivitis outbreaks, suggesting these strains have a predilection for causing conjunctivitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 16 publications
2
27
1
Order By: Relevance
“…In contrast, some serotypes were shown to be carried more than the others (148). Within NT pneumococci, group II NT pneumococci are well known for conjunctivitis outbreaks and NP carriage but are rarely responsible for IPD (112,149,150). The special proteins expressed by group II NTs appear to be important in pneumococcal carriage (111) and adhesion to epithelial cells (151).…”
Section: Serotype and Diseasementioning
confidence: 99%
“…In contrast, some serotypes were shown to be carried more than the others (148). Within NT pneumococci, group II NT pneumococci are well known for conjunctivitis outbreaks and NP carriage but are rarely responsible for IPD (112,149,150). The special proteins expressed by group II NTs appear to be important in pneumococcal carriage (111) and adhesion to epithelial cells (151).…”
Section: Serotype and Diseasementioning
confidence: 99%
“…Four of these strains revealed MLST genotypes identical (ST344, ST448, and ST1186) or similar (ST1540, sharing 5 of 7 alleles with ST344) to those associated with previously-reported conjunctivitis outbreaks [24], [25]. ST1540 was previously recorded from a nontypeable carriage isolate according to the MLST database (http://www.mlst.net).…”
Section: Resultsmentioning
confidence: 96%
“…Multilocus sequence typing revealed that the majority of isolates were the ST448 strain. 6 Finally, an outbreak occurred in March and April 2005 in Saskatchewan, Canada. Fluorescence-based amplified fragment length polymorphism analysis was used to characterize the isolates rather than pulsed-field gel electrophoresis or MLST, so it is unknown if the ST448 strain caused this outbreak, however, like the Dartmouth outbreak, there were no associated cases of pneumonia, and the majority of cases had bilateral eye involvement.…”
Section: Discussionmentioning
confidence: 99%